La dimensione epistolare della lettera ai Galati - Salvatori, Samuele (Liber Annuus, 2024)
Abstract Studies on the letter to the Galatians in recent decades have seen a significant shift in focus from the epistolary perspective to the argumentative one. However, there are notable epistolary elements that suggest Paul’s purpose is not only to persuade the Galatians about the relationship between faith in Christ, justification, and the role of the Mosaic law, but also to restore his relationship with them through constant references to the beginnings of their faith. The aim of this research is to identify the presence and function of these elements within the letter.